2001
DOI: 10.1136/gut.49.2.220
|View full text |Cite
|
Sign up to set email alerts
|

SOX10is abnormally expressed in aganglionic bowel of Hirschsprung's disease infants

Abstract: Background-The primary pathology of Hirschsprung's disease (HD) is a congenital absence of ganglion cells in the caudal most gut. The spastic aganglionic bowel is often innervated by a network of hypertrophied nerve fibres. Recently, mutations of SOX10 have been identified in patients with HD but only in those with Waardenburg-Shah syndrome. Aims-To understand the molecular basis for the pathogenesis of HD we intended to determine the specific cell lineages in the enteric nervous system which normally express … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…It is tempting to speculate that miss-expression of NRG1 could affect the Sox10-mediated maintenance of ENS progenitors and contribute to aganglionosis. In addition, similarly to NRG1, Sox10 is important for defining and maintaining the identity of glial cells in later development stages (43), including the mature human ENS, and abnormal Sox10 expression has been observed in the aganglionic bowel of HSCR patients (44). Whether the latter could be linked to the role proposed above for NRG1 in adult gut and whether they altogether could account for the abnormalities of the extra-cellular matrix characteristic of the aganglionic bowel needs further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…It is tempting to speculate that miss-expression of NRG1 could affect the Sox10-mediated maintenance of ENS progenitors and contribute to aganglionosis. In addition, similarly to NRG1, Sox10 is important for defining and maintaining the identity of glial cells in later development stages (43), including the mature human ENS, and abnormal Sox10 expression has been observed in the aganglionic bowel of HSCR patients (44). Whether the latter could be linked to the role proposed above for NRG1 in adult gut and whether they altogether could account for the abnormalities of the extra-cellular matrix characteristic of the aganglionic bowel needs further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Due to the fact that PGP9.5 is also a pan-neuronal marker, strong efforts have to be undertaken to identify other stemcell markers that will be able to selectively identify neuronal stem cells, ideally at all ages. Interesting candidates such as p75, Phox2b (Young et al 1999), and SOX10 (Bondurand et al 1998;Kapur 1999;Sham et al 2001) were found in various animal models and will be tested in our human samples. …”
Section: Discussionmentioning
confidence: 99%
“…They encompass expression in emerging NCCs and neural crest derivatives (Figure 3; Bondurand et al, 1998;Herbarth et al, 1998;Kuhlbrodt et al, 1998a;Pusch et al, 1998;Southard-Smith et al, 1998;Kapur, 1999), including the enteric ganglia of HSCR patients (Sham et al, 2001b) and mouse embryos (Figure 3), and expression in the and Site inner ear during mouse development (Watanabe et al, 2000). The Sox10 Dom heterozygous mice show enteric aganglionosis (megacolon) and hypopigmentation phenotypes characteristic of WS-IV.…”
Section: /Sox1mentioning
confidence: 99%